Molybdenum-mediated N2-splitting and functionalization in the presence of a coordinated alkyne - Wagner, Hannah; Wadepohl, Hubert; Ballmann, Joachim (Angewandte Chemie. International edition, 2021)
A new [PCCP]-coordinated molybdenum platform comprising a coordinated alkyne was employed for the cleavage of molecular dinitrogen. The coordinated η2-alkyne was left unaffected during this reduction. DFT calculations suggest that the reaction proceeds via an initially generated terminal N2-complex, which is converted to a dinuclear μ-(η1:η1)-N2-bridged intermediate prior to N−N bond cleavage. Protonation, alkylation and acylation of the resulting molybdenum nitrido complex led to the corresponding N-functionalized imido complexes. Upon oxidation of the N-acylated imido derivative in MeCN, a fumaronitrile fragment was built up via C−C coupling of MeCN to afford a dinuclear molybdenum complex. The key finding that the strong N≡N bond may be cleaved in the presence of a weaker, but spatially constrained C≡C bond contradicts the widespread paradigm that coordinated alkynes are in general more reactive than gaseous N2.
Im Titel ist die Ziffer "2" beim Ausdruck "N2-splitting" tiefgestellt
Gesehen am 02.09.2022